PREVALENCE AND SEVERITY OF POSSIBLE DRUG-DRUG INTERACTIONS AMONG THE GERIATRIC PATIENTS AT AN INDIAN TERTIARY CARE TEACHING HOSPITAL - Sripada, Ramam; Kumar Sv, Suresh; N, Devanna; Ravindra Reddy, Kandula (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to study the prevalence and severity of possible drug-drug interactions (DDIs) among the geriatric patients. Methods: The present study was a retrospective cross-sectional study. Case records of geriatric inpatients from the medical records department were included in the study and the case records of all the remaining age group inpatients were excluded from the study. All the collected cases were subjected to check for the DDIs using the software Micromedex 2.0 and were categorized into minor, moderate, and major based on the severity. Results: In this study, a total of 85 cases were screened for possible DDIs, and among them, 54 cases were found to be with 179 possible DDIs. The prevalence was observed to be 63.5%. Most of the possible DDIs were found to be with moderate severity (65.4%) followed by major (25.7%). Majority of the possible DDIs were observed in the Department of General Medicine (83.2%) followed by chest and tuberculosis (7.8%). Conclusion: Majorly, the severity of interactions was found to be moderate in this study. To reduce the DDIs, rationale prescriptions have to be prescribed by considering the risk-benefit ratio. Geriatrics should be prescribed very cautiously because the age-related pharmacokinetics plays a significant role. By taking all the above aspects into consideration, clinical pharmacist should play a crucial role in the prevention and management of DDIs, especially in geriatrics. Â